2008
DOI: 10.1071/mf08044
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in burrow morphology of the mud shore crab Helograpsus haswellianus (Brachyura, Grapsidae) in South Australian saltmarshes

Abstract: Burrowing by crabs is an important component of their functional role in mangrove and saltmarsh habitats. The grapsid crab Helograpsus haswellianus (Whitelegge, 1889) is one of the more conspicuous burrowing organisms in the saltmarshes of southern Australia. To evaluate intraspecific differences in burrowing behaviour among saltmarshes on a regional scale, we compared vegetation cover, sediment composition and burrow morphology at four sites using resin casts. Six burrow morphology characters were measured (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Moreover, in MCL, chambers can be constructed along the length of the burrow, while in SAO chambers may be constructed at the entrance, as widened entries, due to their short length of the burrows. This pattern of variation in the burrow form associated with habitat characteristics as the sediment composition was also reported for other grapsoids such as Austrohelice crassa (Morrisey et al 1999;Needham et al 2010) and Helograpsus haswellianus (Katrak et al 2008). Similarly, studies conducted on thalassinidean shrimps found deeper burrows in muddy shore habitats compared to sandy ones, indicating that sediment type aVects the burrow features (GriYs and Chavez 1988;Li et al 2008).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, in MCL, chambers can be constructed along the length of the burrow, while in SAO chambers may be constructed at the entrance, as widened entries, due to their short length of the burrows. This pattern of variation in the burrow form associated with habitat characteristics as the sediment composition was also reported for other grapsoids such as Austrohelice crassa (Morrisey et al 1999;Needham et al 2010) and Helograpsus haswellianus (Katrak et al 2008). Similarly, studies conducted on thalassinidean shrimps found deeper burrows in muddy shore habitats compared to sandy ones, indicating that sediment type aVects the burrow features (GriYs and Chavez 1988;Li et al 2008).…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, in many crab species, the distribution of shelters or the type of habitat used for the construction of burrows plays an important role in mating as an adaptation to the particular habitat in which the individual lives (Seiple and Salmon 1982;Salmon 1983;Wirtz and Diesel 1983;Abele et al 1986;Christy 1987;Lindberg and Stanton 1989). Detailed studies describing burrow architecture demonstrate that it varies according to the diVerent habitat sediment composition (Morrisey et al 1999;Katrak et al 2008;Li et al 2008;Needham et al 2010). In addition, several studies of ocypodids show that the burrow form is diVerent between sexes, having an enlarged terminal chamber where matings occur in male burrows (Christy 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Density variations in intertidal crabs were shown to be related to sediment grain size (Katrak et al 2008, Wang et al 2009). Seiple (1979) found that Sesarma cinereum habitats were characterized by sandy substrates, whereas S. reticulatum inhabited substrates with high silt content.…”
Section: Environmental Factors Influencing the Crab Distributionmentioning
confidence: 99%
“…The burrowing activity is widespread among crabs from intertidal soft-bottom habitats and provides a refuge from subtidal or aerial predators (Warren 1990;Fathala et al 2010a, b). Even when the morphology of burrows is species-speciWc (GriYs and Suchanek 1991), it can vary intraspeciWcally in relation to trophic modes, sediment type, tidal level, water table depth, and structures on and under soil (Iribarne et al 1997;Katrak et al 2008;Sal Moyano et al in press). The tidal pattern of each site results from diVerent amplitudes and regularity of submersion events.…”
Section: Discussionmentioning
confidence: 99%